Droughts, distress, and policies for drought proofing agriculture in Bihar, India - Kishore, Avinash; Joshi, Pramod Kumar; Pandey, Divya (International Food Policy Research Institute, 2014)
This study was undertaken to assess if various drought-proofing and drought-relief programs are effective in mitigating the impact of droughts on crop production and household consumption in rural Bihar, India. This study is relevant as Bihar has experienced four drought years since 2009. The drought in 2009 led to an increase in the number of poor people in the state from 2004-2005 to 2009-2010, in spite of rapid growth of gross domestic product in this period. The government of Bihar runs a number of drought-proofing and drought-relief programs to mitigate the impact of drought, but with little effect. The two largest social safety net programs-the Targeted Public Distribution System (TPDS) and the Mahatma Gandhi National Rural Employment Guarantee Scheme (MGNREGS)-provide little relief to drought-affected families in rural Bihar. Additional subsidy on diesel to irrigate Kharif crops in drought-affected areas does not reach many farmers. Delays, uncertainties, and high transaction costs in its disbursal to farmers further reduce the subsidy’s effectiveness. Public tubewells and subsidy on private wells and pump-sets fail to provide wide-scale relief for the drought-stricken area. The results of our year-long study of 160 farmers with access to cheap irrigation from solar powered pump-sets in Bihar showed that these farmers grew paddy in all their land in Kharif in 2013, in spite of low rainfall.